1991
DOI: 10.1007/bf01448334
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of positively charged cobalt cluster ions with CH4, N2, H2, C2H4, and C2H2

Abstract: Abstract. Reactivity of positively charged cobalt cluster ions (Co ], n = 2-22), produced by laser vaporization, with various gas samples (CH4, Nz, H2, C2H4, and C2Hz) were systematically investigated by using a fast-flow reactor. The reactivity of Co,, + with the various gas samples is qualitatively consistent with the adsorption rate of the gas to cobalt metal surfaces. Co. + highly reacts with C2H2 as characterized by the adsorption rate to metal surfaces, and it indicates no size dependence. In contrast, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
34
0
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 24 publications
4
34
0
1
Order By: Relevance
“…On the other hand, Co n + exhibits sharp cross-section peaks at n = 15 and 26. The local maximum at n = 15 is consistent with a maximum of n = 15 in the relative efficiency of chemisorption of C 2 H 4 on Co n + ͑n =3-22͒ measured in a fast flow reactor experiment by Nakajima et al 60 …”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…On the other hand, Co n + exhibits sharp cross-section peaks at n = 15 and 26. The local maximum at n = 15 is consistent with a maximum of n = 15 in the relative efficiency of chemisorption of C 2 H 4 on Co n + ͑n =3-22͒ measured in a fast flow reactor experiment by Nakajima et al 60 …”
Section: Resultssupporting
confidence: 78%
“…Motivated by such surface reactions, several research groups have studied reactions of iron-group metal clusters with ethylene molecules. Nakajima et al have studied reactions of cobalt cluster ions, Co n + ͑n =2-22͒, with ethylene molecules in a fast flow reactor, 60 and have found that Co n + ͑n =4, 5, and 10-15͒ have particularly high reaction rates. Irion and coworkers have studied reactions of iron cluster ions, Fe n + ͑n =2-13͒, with ethylene molecules in FTICR.…”
Section: Introductionmentioning
confidence: 98%
“…This behavior was observed for all cluster sizes studied, except for ) was again higher than the value of the corresponding mono-carbonyl complex. The initial decrease of ν(CO) correlates with a particular low reactivity of these clusters towards hydrogen [11] . For the small clusters the shift of ν(CO) is linear with hydrogen coverage and the slope decreases as the clusters become larger.…”
mentioning
confidence: 95%
“…Recently, Nakajima et al [7] have reported the relative reactivity of positively charged cobalt clusters (Co~, n = 3-22) with H2. Absolute rate constants have been measured in the size range n = 7-68 at 293 K. The rate constants are found to be a strong function of cluster size, varying by a factor of 400.…”
mentioning
confidence: 99%